ANALISIS BUTIR SOAL UJIAN AKHIR SEKOLAH PRODUKTIF PEMASARAN KELAS XII PEMASARAN SMK NEGERI 9 SEMARANG - Raharja, Nicky Soerya (Economic Education Analysis Journal, 2014)
Tujuanpenelitianiniyaituuntukmengetahuivaliditas soal, reliabilitas soal, daya pembeda soal, tingkat kesukaran soal dan efektifitas distraktorujianakhirsekolahproduktifpemasaran. Populasi dalam penelitian ini adalah lembar jawab ujian akhir sekolahProduktif Pemasaran kelas XIIPemasaran SMK N 9 Semarang yang berjumlah 100 lembar. Variabel yang dikajidalampenelitianiniyaitukualitassoalberupavaliditas soal, reliabilitas soal, daya pembeda soal, tingkat kesukaran soal dan efektifitas distraktor. Pengumpulan data dilakukandengancaradokumentasi. Teknikanalisis data menggunakanprogram ANATES V4.Hasil penelitian soal UjianAkhirSekolah Produktif Pemasaran Kelas XII Pemasaran SMK Negeri 9 Semarang (StudiPadaTahun Ajaran 2013/2014) termasuk kategori validitas sangat rendah (54%), tergolong soal tidak reliable (Alpha = 0.63), daya pembeda jelek (56%), tingkat kesukaran sedang (40%), dan termasuk kategori dengan efektifitas distraktor yang jelek (62%tidakberfungsi).Kesimpulanpenelitianiniyaitu soalUjian Akhir Sekolah Produktif Pemasaran Kelas XII Pemasaran SMK Negeri 9 Semarang (StudiPadaTahun Ajaran 2013/2014) belum memiliki kualitas sesuai standar. Saran yang berkaitan dengan hasil penelitian ini yaitu. Dalampembuatansoalperludiperhatikankevalidansoal, reliabilitas soal,tingkatkesukaran, dayapembeda, efektifitasdistraktornyasehinggasoaltersebutbenar-benarmenggambarkanhasiltes yang sebenarnya.The purpose of this study is to find out the validity, reliability, distinguishing power, the range of difficulty of the test and the effective distracter of the final examination of productive marketing class. The population of this study is the worksheet of the students which is about 100 sheets in productive marketing class grade XII SMK 9 Semarang. The variables of this study are the quality of the test which shows the validity, the reliability, the range of difficulty of the test and the distracter. The data were collected by doing the documentation. The technique of analyzing data is using the ANATES V4 program. The result of the study for the final examination test of Productive Marketing Class grade XII SMK 9 Semarang on 2013/2014 shows that the validity of the test is poor which is about 54 %, the test is not reliable (alpha=0.63), the distinguishing power is poor (56%), the range of difficulty is medium (40%) and the test is also categorized of having poor distracter effectiveness (62% disfunctioned). The conclusion is that the quality of the final examination test for Productive Marketing Class grade XII SMK 9 Semarang 2013/2014 is not yet according to standard. The suggestions related to the result of the study are it is important to give more attention to the process of creating the valid test, to make the test more reliable, not to mention the range of difficulty and the distinguishing power, also the effectiveness of the distracter, so that the final examination test will shows the real result of students comprehending. The purpose of this study is to find out the validity, reliability, distinguishing power, the range of difficulty of the test and the effective distracter of the final examination of productive marketing class. The population of this study is the worksheet of the students which is about 100 sheets in productive marketing class grade XII SMK 9 Semarang. The variables of this study are the quality of the test which shows the validity, the reliability, the range of difficulty of the test and the distracter. The data were collected by doing the documentation. The technique of analyzing data is using the ANATES V4 program. The result of the study for the final examination test of Productive Marketing Class grade XII SMK 9 Semarang on 2013/2014 shows that the validity of the test is poor which is about 54 %, the test is not reliable (alpha=0.63), the distinguishing power is poor (56%), the range of difficulty is medium (40%) and the test is also categorized of having poor distracter effectiveness (62% disfunctioned). The conclusion is that the quality of the final examination test for Productive Marketing Class grade XII SMK 9 Semarang 2013/2014 is not yet according to standard. The suggestions related to the result of the study are it is important to give more attention to the process of creating the valid test, to make the test more reliable, not to mention the range of difficulty and the distinguishing power, also the effectiveness of the distracter, so that the final examination test will shows the real result of students comprehending.